Molecular profiling of solid tumors by next-generation sequencing: an experience from a clinical laboratory - Bhai, Pratibha; Turowec, Jacob; Santos, Stephanie; Kerkhof, Jennifer; Pickard, LeeAnne; Foroutan, Aidin; Breadner, Daniel; Cecchini, Matthew; Levy, Michael A.; Stuart, Alan; Welch, Stephen; Howlett, Christopher; et al. (Frontiers in Oncology, 2023)
Background: Personalized targeted therapies have transformed management of several solid tumors. Timely and accurate detection of clinically relevant genetic variants in tumor is central to implementation of molecular targeted therapies. To facilitate precise molecular testing in solid tumors, targeted next generation sequencing (NGS) assays have emerged as a valuable tool. In this study, we provide an overview of the technical validation, diagnostic yields, and spectrum of variants observed in 3164 solid tumor samples that were tested as part of the standard clinical diagnostic assessment in an academic healthcare institution over a period of 2 years. Methods: Ion Ampliseq™ Cancer Hotspot Panel v2 assay (ThermoFisher) that targets ~2,800 COSMIC mutations from 50 oncogenes and tumor suppressor genes were validated and a total of 3164 tumor DNA samples were tested in two years. 500 tumor samples were tested by the comprehensive panel containing all the 50 genes. Other samples, including 1375 lung cancer, 692 colon cancer, 462 melanoma, and 135 brain cancer, were tested by tumor - specific targeted subpanels including a few clinically actionable genes: Results: 2016/3164 (63.7%) patient samples tested positive for at least one clinically relevant variant. 290/500 sample tested by comprehensive panel, had a clinically relevant variant with TP53, KRAS and PIK3CA being the most frequently mutated genes. The diagnostic yield in major tumor types were: Breast (58.4%), colorectal (77.6%), lung (60.4%), pancreatic (84.6%), endometrial (72.4%), Ovary (57.1) %, and thyroid (73.9%). Tumor specific targeted subpanels also demonstrated high diagnostic yields: Lung (69%); Colon (61.2%), Melanoma (69.7%), and Brain (20.7%). Co-occurrence of mutations in more than one gene was frequently observed. Conclusions: Findings of our study demonstrate the feasibility of integrating an NGS-based gene panel screen as part of a standard diagnostic protocol for solid tumor assessment. High diagnostic rates enable significant clinical impact including improved diagnosis, prognosis and clinical management in patients with solid tumors.